Developments in Teaching Authority since Vatican II - Sullivan, Francis A. (Theological studies, 2012)
The author describes and comments on developments that have taken place since Vatican II with regard to teaching authority. Among subjects exercising such authority he treats episcopal conferences and the Congregation for the Doctrine of the Faith. Among objects of definitive teaching he treats truths that are not revealed but necessarily connected with revealed truth. As a way of exercising teaching authority, he discusses papal declarations that a doctrine has been taught infallibly by the ordinary universal magisterium.